Development of a novel electrochemical carboxylation system using a microreactor. Issue 119 (19th November 2015) - Tateno, Hiroyuki; Matsumura, Yoshimasa; Nakabayashi, Koji; Senboku, Hisanori; Atobe, Mahito
Abstract : We have developed an novel electrochemical carboxylation system using a microreactor. In this system, electrochemical carboxylation of benzyl halides proceeds without the use of a sacrificial anode to give carboxylated products in excellent yields. Abstract : We have developed a novel electrochemical carboxylation system for CO2 fixation to benzyl halides using a microreactor. In this system, electrochemical carboxylation of benzyl halides proceeded very efficiently without the use of a sacrificial anode such as a Mg anode to give carboxylated products in excellent yields.